Sustainable Architecture in Domestic Liquid Waste Management for Environmental Health - Qurrota Aýun, Ghina Rizqandi; Nurdiawati, Ela (RUSTIC, 2026)
Harjatani Heritage Estate is a residential area located in Margatani Village, Serdang, Kramatwatu, Serang Regency. One of the main issues in this housing area is the poorly organized wastewater drainage system, caused by inadequate drainage flow in the surrounding environment, which has the potential to pollute the area with domestic wastewater. Domestic wastewater, commonly referred to as greywater, originates from household activities such as bathing, washing, and kitchen use. Waste management, both domestic and industrial, remains a serious environmental challenge in Indonesia. One alternative approach to addressing this issue is through natural wastewater management integrated into sustainable architectural planning for environmental health. This study employs a qualitative research method using observational techniques and data analysis. The analysis includes site conditions, surrounding environmental characteristics, and landscape planning as an application of sustainable architecture principles, supported by AutoCAD-based design exploration and interviews with local community representatives. The results indicate that landscape planning plays a significant role in supporting sustainable architecture as an environmentally responsive solution for domestic wastewater management.